PENGARUH PEMBERIAN PUPUK ORGANIK CAIR (POC) URINE DOMBA TERHADAP PERODUKTIPITAS RUMPUT ODOT (Pennisetum Purpureum Cv. Mott) SETELAH DEPOLISASI - Ilham, Ilham; Media Agus Kurniawan (Journal of Innovation Research and Knowledge, 2024)
: The study aims to determine theeffect of sheep urine manure on tht Pennisetum purpureum cv. Mott grass after the first defoliation. The data analysis method used in this research is a Urine Manure Design (UMD) Non-Factorial consisting of 4 treatments and 5 replications, namely P0 (Without Urine application), P1 (Urine manure application every 2 days), P2 (Urine manure application every 3 days), and P3 (Urine manure application every 5 days). The parameters observed in this study are the number of tillers, plant height, and fresh material production. The results of the study show that treatment P1 is the best treatment in terms of fresh material production, plant height, and number of tillers of Pennisetum purpureum cv. Mott grass with Urine manure application after the first defoliation, with the number of tillers of Pennisetum purpureum cv. Mott grass being 4.88/polybag, plant height being 65.40 cm/polibag, and fresh material production being 216.84 grams/polybag